2008
DOI: 10.1038/sj.bjc.6604487
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and risk of pancreatic cancer among postmenopausal women: the Women's Health Initiative (United States)

Abstract: A total of 138 503 women in the Women's Health Initiative in the United States were followed (for an average of 7.7 years) through 12 September 2005 to examine obesity, especially central obesity in relation to pancreatic cancer (n ¼ 251). Women in the highest quintile of waist-to-hip ratio had 70% (95% confidence interval 10 -160%) excess risk of pancreatic cancer compared with women in the lowest quintile. (Ekbom and Hunter, 2007). Besides tobacco smoking and chronic pancreatitis (Lowenfels et al, 1999), li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 40 publications
2
24
0
2
Order By: Relevance
“…We might not have captured critical windows of lifetime weight change that may confer a higher risk of pancreatic cancer, particularly among former smokers. Central adiposity may be a more relevant measure than BMI for risk of pancreatic cancer [8, 44, 45, 5052]. AARP, BCDDP, and SWHS collected waist and hip circumference information, but the number of cases in the BCDDP or SWHS cohorts with such data was small (<60) so that the associations with central adiposity would be driven by the AARP study, for which a positive association was previously reported for women but not for men [8].…”
Section: Discussionmentioning
confidence: 99%
“…We might not have captured critical windows of lifetime weight change that may confer a higher risk of pancreatic cancer, particularly among former smokers. Central adiposity may be a more relevant measure than BMI for risk of pancreatic cancer [8, 44, 45, 5052]. AARP, BCDDP, and SWHS collected waist and hip circumference information, but the number of cases in the BCDDP or SWHS cohorts with such data was small (<60) so that the associations with central adiposity would be driven by the AARP study, for which a positive association was previously reported for women but not for men [8].…”
Section: Discussionmentioning
confidence: 99%
“…This study examined obesity, especially central obesity, in relation to PC (n=251) for the duration of an average of 7.7 years of follow-up [40]. The results show that women in the highest quintile of waist-to-hip ratio have a 70 percent (95% CI, 10–160%) greater risk of PC compared with women in the lowest quintile.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal obesity may be more strongly associated with insulin resistance than peripheral obesity (4), but there have been relatively few studies of waist circumference and waist-to-hip ratio as measures of abdominal fatness in relation to pancreatic cancer risk. A number of additional large cohort studies have been published since the WCRF/AICR report from 2007 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), thus, we conducted an updated meta-analysis of BMI, waist circumference and waist-to-hip ratio and pancreatic cancer risk with the aim to clarify whether body fatness is associated with pancreatic cancer in both men and women and in European and Asian populations as well. In addition, we wanted to clarify the dose-response relationship between BMI, waist circumference and waist-to-hip ratio and pancreatic cancer risk by conducting nonlinear dose-response analyses and by restricting the analysis to studies among non smokers or never smokers.…”
Section: Introductionmentioning
confidence: 99%